Increased Risk of Congestive Heart Failure Following Carbon Monoxide Poisoning. (19th April 2021) - Huang, Chien-Cheng; Chen, Tzu-Hao; Ho, Chung-Han; Chen, Yi-Chen; Hsu, Chien-Chin; Lin, Hung-Jung; Wang, Jhi-Joung; Chang, Ching-Ping; Guo, How-Ran
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Carbon monoxide poisoning (COP) is an important public health issue around the world. It may increase the risk of myocardial injury, but the association between COP and congestive heart failure (CHF) remains unclear. We conducted a study incorporating data from epidemiological and animal studies to clarify this issue. Methods: Using the National Health Insurance Database of Taiwan, we identified patients with COP diagnosed between 1999 and 2012 and compared them with patients without COP (non-COP cohort) matched by age and the index date at a 1:3 ratio. The comparison for the risk of CHF between the COP and non-COP cohorts was made using Cox proportional hazards regression. We also established a rat model to evaluate cardiac function using echocardiography and studied the pathological changes following COP. Results: The 20 942 patients in the COP cohort had a higher risk for CHF than the 62 826 members in the non-COP cohort after adjusting for sex and underlying comorbidities (adjusted hazard ratio, 2.01 [95% CI, 1.74–2.32]). The increased risk of CHF persisted even after 2 years of follow-up (adjusted hazard ratio, 1.85 [95% CI, 1.55–2.21]). In the animal model, COP led to a decreased left ventricular ejection fraction on echocardiography and damage to cardiac cells with remarkable fibrotic changes. Conclusions: Our epidemiological data showed an increased risk of CHF was associated with COP, which was supported by the animal study. We suggest close follow-up of cardiac function for patients with COP to facilitate early intervention and further studies to identify other long-term effects that have not been reported in the literature.